Bowel viability assessment during surgery (review of the literature) - A. A. Zacharenko; M. A. Belyaev; A. A. Trushin; D. A. Zaytcev; R. V. Kursenko (Вестник хирургии имени И.И. Грекова, 2020)
The problem of bowel viability assessment during surgery is still opened. High value predictive and economically available technique is thought to decrease postoperative morbidity and mortality during elective and urgent abdominal surgery. To evaluate the available techniques for intraoperative bowel viability assessment, the search of Russian and foreign up-to-date literature was performed. Parameters of techniques are analyzed: intraoperative clinical application, invasiveness, objectivity and quantification of viability parameters, predictive value for necrosis and anastomotic leakage. There is still no standardised and available for every operative theatre method for bowel viability assessment during surgery. Numerous of techniques such as near-infrared fluorescence (NIR) angiography, using indocyanine green (ICG), optical coherence tomography (OCT), laser doppler flowmetry (LDF) are proposed to be more evaluated and perspective. Autofluorescence spectroscopy for NADH and flavoproteins seems to be a promising tool for early detection of nonviable bowel segments.